2021
DOI: 10.3390/ma14040897
|View full text |Cite
|
Sign up to set email alerts
|

Fibre Bragg Grating Based Acoustic Emission Measurement System for Structural Health Monitoring Applications

Abstract: Fiber Bragg grating (FBG)-based acoustic emission (AE) detection and monitoring is considered as a potential and emerging technology for structural health monitoring (SHM) applications. In this paper, an overview of the FBG-based AE monitoring system is presented, and various technologies and methods used for FBG AE interrogation systems are reviewed and discussed. Various commercial FBG AE sensing systems, SHM applications of FBG AE monitoring, and market potential and recent trends are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…In order to improve the sensitivity, the high reflectivity slope of the FBG sensor is often utilized to change the intensity or the total energy or the system output. An excellent description of different edge slope configurations can be found here [17]. In the powerbased approach, a broadband laser followed by an optical filter is used to focus the light wavelength to have a overlap with the reflected spectrum of the FBG.…”
Section: Wavelength-based Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve the sensitivity, the high reflectivity slope of the FBG sensor is often utilized to change the intensity or the total energy or the system output. An excellent description of different edge slope configurations can be found here [17]. In the powerbased approach, a broadband laser followed by an optical filter is used to focus the light wavelength to have a overlap with the reflected spectrum of the FBG.…”
Section: Wavelength-based Sensorsmentioning
confidence: 99%
“…This paper tries to present the state of the art in the use of FO sensors for ultrasonic-based SHM techniques. Two review papers that focused on FBG sensors for ultrasonic measurements [16,17] have recently been published. Although these review papers cover a lot of papers in the field, they do not provide an overview of sensors other than FBG sensors.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the existing methods and means for determining the degradation of the mechanical properties of materials during the operation of structures in real time showed that they are all intended for the study of one type of deformation: tension [ 37 , 38 , 39 ] or bending [ 40 , 41 , 42 , 43 ], while under real conditions loading forces act on the material, under combined conditions of deformation [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Relative Workmentioning
confidence: 99%
“…Therefore, in the practical application of AE detection, it is necessary to design a sensitization structure to improve its sensitivity in the detection of structural damage. The sensitivity enhancement structure of FBG sensor [8] protects the bare grating to avoid damage, and even achieve temperature compensation [9,10] or sensitivity adjustability [11] as required. Thus, the sensitivity enhancement structure of FBG AE sensor is the key to its engineering application and becomes a hot research issue in the application field of AE technology [12,13].…”
Section: Introductionmentioning
confidence: 99%